Patterns of Medical Problems Among Rohingya Refugees Attending IMARET4Rohingya Clinics in Kelantan and Selangor - Abdul Hai, Aina Haziqah; Tahir, Ahmad Rashidi Mohamed; Athirah Daud, Nur Aizati (International Journal of Human and Health Sciences (IJHHS), 2022)
a